Efficacy of daratumumab combination regimen in patients with multiple myeloma: A combined analysis of phase III randomized controlled trials. Issue 1 (23rd June 2020) - Htut, Thura W.; Thein, Kyaw Z.; Lawrie, Alastair; Tighe, Jane; Preston, Gavin
Abstract: The use of the CD38 monoclonal antibody daratumumab in combination with standard myeloma chemotherapy regimens has been studied extensively in recent years. We undertook an updated meta‐analysis of phase III randomized controlled trials (RCT) to determine the efficacy of daratumumab combination regimens. The relative risk for progression was significantly lower in daratumumab‐treated cohorts (HR 0.46, 95% CI 0.38‐0.55) and this was consistent across newly diagnosed and relapsed cases. No statistically significant improvement was identified in newly diagnosed patients with high‐risk cytogenetics and this group remains a therapeutic challenge.